2023
DOI: 10.48550/arxiv.2301.11937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AGN Feeding and Feedback in M84: From Kiloparsec Scales to the Bondi Radius

Abstract: We present the deepest Chandra observation to date of the galaxy M84 in the Virgo Cluster, with over 840 kiloseconds of data provided by legacy observations and a recent 730 kilosecond campaign. The increased signal-to-noise allows us to study the origins of the accretion flow feeding the supermassive black hole in the center of M84 from the kiloparsec scales of the X-ray halo to the Bondi radius, 𝑅 B . Temperature, metallicity, and deprojected density profiles are obtained in four sectors about M84's AGN, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 120 publications
1
2
0
Order By: Relevance
“…Observations of M87 (Russell et al 2015) suggested there are two significant temperature components within 2 kpc and did not find evidence for a temperature increase within ∼0.25 kpc. The flat temperature profile is also reported in observations of the galaxy M84 (Bambic et al 2023). This is consistent with our simulations.…”
Section: Radial Profilessupporting
confidence: 93%
“…Observations of M87 (Russell et al 2015) suggested there are two significant temperature components within 2 kpc and did not find evidence for a temperature increase within ∼0.25 kpc. The flat temperature profile is also reported in observations of the galaxy M84 (Bambic et al 2023). This is consistent with our simulations.…”
Section: Radial Profilessupporting
confidence: 93%
“…An even more complex example can be found in the Perseus Galaxy Cluster (Fabian et al 2017), which shows off-axis cavities, rims, and a geometrically complex distribution of pressure waves (also see Ubertosi et al 2022, for the RBS 797 galaxy cluster). Other galaxy groups or clusters with such intricate cavity structures include, for example, M84 (Bambic et al 2023), NGC 5813 (Randall et al 2015), A2052 (Blanton et al 2011), NGC 5044 (David et al 2011, Cygnus A (Smith et al 2002), MS0735.6+7421 (McNamara et al 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Observations in galaxy clusters like Perseus show off-axis cavities, rims, and intricate pressure wave distributions (Fabian et al, 2017). Similarly complex structures are observed in other systems such as M84 (Bambic et al, 2023), NGC 5813 (Randall et al, 2015), A2052 (Blanton et al, 2011), NGC 5044 (David et al, 2011), Cygnus A (Smith et al, 2002), MS0735.6 + 7,421 (McNamara et al, 2009. This complexity in 1 A better estimate may be the AlfvΓ©n time scale cavity structures may indicate deflections in the path of the jets involved, highlighting a possible jet reorientation phenomenon.…”
Section: X-ray Cavities Associated With the Xrgsmentioning
confidence: 76%